Design and Implementation of Management Information System for University Library - Zhou, Wei (International Journal of Computer Science and Information Technology, 2024)
With the rapid development of the Internet, information processing work in universities has also increased, from libraries to electronic book management platforms, everything is available. Although the number of libraries we have is constantly increasing and people’s attention to them is also increasing, their existence is often universal, non-existent, and sometimes incomplete, which brings great difficulties to our daily management. Analyzed the workflow and functional requirements of university libraries, and applied them in practice to achieve better results. On this basis, the paper provides a detailed analysis of the main functions and various forms of the enterprise financial management information system. SQL Server 2008 is a database based system with high confidentiality and large-scale storage capacity. Through this concept and approach, one can better grasp and grasp the business skills required in daily work and work, greatly improving work efficiency. A library MIS based on AIS/S model was constructed using an A/S model and a SQL Server database. This software is user centered and librarian centered. They proposed a system to the library that maximized its workflow and improved its service management and supply.